As you like it - Shaughnessy, Robert, 1962- (Shakespeare in performance., 2018)
This book examines the modern performance history of one of Shakespeare's best-loved and most enduring comedies, and one that has given opportunities for generations of theatre-makers and theatre-goers to explore the pleasures of pastoral, gender masquerade and sexual ambiguity. Powered by Shakespeare's greatest female comic role, the play invites us into a deeply English woodland that has also been richly imagined as a space of dreams. The study retrieves the untold stories of stage productions in Britain, France and Germany, which include Royal Shakespeare Company productions starring Vanessa Redgrave, Eileen Atkins and Juliet Stevenson, the ground-breaking all-male productions at the National Theatre in 1967 and by Cheek by Jowl in 1992, and the versions directed by Jacques Copeau in Paris in 1934, and by Peter Stein in Berlin in 1977. It also addresses the four major screen versions of the play, ranging from Paul Czinner's 1936 film to Kenneth Branagh's seventy years later